2018
DOI: 10.1186/s12917-018-1360-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol modulates inflammatory responses in LPS-stimulated RAW264.7 cells via the NF-κB and MAPK pathways

Abstract: BackgroundThe uteruses of most dairy cattle are easily infected by bacteria, especially gram-negative bacteria, following parturition. Macrophages are important cells of the immune system and play a critical role in the inflammatory response. In addition, cortisol levels become significantly increased due to the stress of parturition in dairy cattle, and cortisol is among the most widely used and effective therapies for many inflammatory diseases. In this study, we assessed the anti-inflammatory effects and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Stress hormones serve as beacons that make the immune system ready for potential challenges perceived by the brain. Nevertheless, the homeostasis of this system may break down if the enhanced immune response is dysregulated after long activation, as seen during chronic stress [ 32 , 33 , 41 , 42 ].…”
Section: Neuroendocrine Responses To Stressmentioning
confidence: 99%
“…Stress hormones serve as beacons that make the immune system ready for potential challenges perceived by the brain. Nevertheless, the homeostasis of this system may break down if the enhanced immune response is dysregulated after long activation, as seen during chronic stress [ 32 , 33 , 41 , 42 ].…”
Section: Neuroendocrine Responses To Stressmentioning
confidence: 99%
“…Others have shown that the extracellular receptor kinase (ERK) and Janus kinase (JNK) pathways in membranes produce inflammation at term and preterm parturition [ 21 ]. Regardless of signaling pathways, NF-kB activation and an increase in proinflammatory mediators are the final effectors of parturition [ 22 , 23 , 24 , 25 ]. This is a natural and physiological response at term, but is pathologic and prematurely activated in preterm parturitions.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) was used to model inflammation as it stimulates inflammatory cells of the immune system . LPS is a pathogenic endotoxic component in the outer membrane of Gram‐negative bacteria and can disturb the balance between immunity and inflammatory response . LPS stimulation triggers production of proinflammatory cytokines such as tumor necrosis factor alpha (TNFα) and interleukin 6 (IL‐6), which mediate septic shock and acute lung inflammation .…”
Section: Introductionmentioning
confidence: 99%